Presence of a home cage running wheel, but not wheel running per se, decreases social motivation in adult C57BL/6J female mice - Patryk Ziobro; Cassidy A. Malone; Stephen Batter; Longao Xu; Selina B. Xu; Alina Loginov; Katherine A. Tschida (PLoS ONE, 2026)
Physical activity offers myriad benefits to health and well-being, in humans and other animals as well. In rodents, voluntary wheel running can attenuate the effects of both physical and social stressors on rodent social behavior. Whether wheel running affects rodent social behaviors per se remains less well understood. We conducted the current study to test whether home cage access to running wheels impacts the social behaviors of adult, group-housed C57BL/6J female mice during same-sex interactions with novel females. Group-housed females were either given continuous home cage running wheel access or a standard paper hut starting at weaning, and as adults, social behaviors were measured during interactions with novel females. In two cohorts, we found that 5 weeks of running wheel access during adolescence reduced the time that subject females spent investigating a novel female and also tended to reduce total ultrasonic vocalizations produced during interactions. These effects were not reversed by a 2-week period of running wheel removal but were recapitulated in a different cohort by 2 weeks of running wheel access in adulthood. Unexpectedly, we found that these effects on female social behavior were not due to wheel running per se, because females raised from weaning with ‘immobile’ running wheels also showed low rates of social behaviors during same-sex interactions in adulthood. Overall, we find that the presence of a running wheel in the home cage has an enduring inhibitory influence on female social behavior during same-sex interactions, a finding that has implications for the design of studies that include same-sex interactions between female mice.